2017
DOI: 10.1002/glia.23135
|View full text |Cite
|
Sign up to set email alerts
|

Microglial repopulation resolves inflammation and promotes brain recovery after injury

Abstract: Microglia mediate chronic neuroinflammation following central nervous system (CNS) disease or injury, and in doing so, damage the local brain environment by impairing recovery and contributing to disease processes. Microglia are critically dependent on signaling through the colony-stimulating factor 1 receptor (CSF1R) and can be eliminated via administration of CSF1R inhibitors. Resolving chronic neuroinflammation represents a universal goal for CNS disorders, but long-term microglial elimination may not be am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
178
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 184 publications
(186 citation statements)
references
References 44 publications
6
178
2
Order By: Relevance
“…As we and others have reported, PLX5622 administration robustly reduced the presence of Iba1 + microglia (Figure b) (McKim et al, ; Rice et al, ; Rice et al, ). Indeed, 21 day administration of PLX5622 resulted in an ~97% reduction of the number of Iba1 + microglia compared to vehicle‐fed controls (Figure c, F 1,10 = 271.233; p < .001).…”
Section: Resultssupporting
confidence: 78%
“…As we and others have reported, PLX5622 administration robustly reduced the presence of Iba1 + microglia (Figure b) (McKim et al, ; Rice et al, ; Rice et al, ). Indeed, 21 day administration of PLX5622 resulted in an ~97% reduction of the number of Iba1 + microglia compared to vehicle‐fed controls (Figure c, F 1,10 = 271.233; p < .001).…”
Section: Resultssupporting
confidence: 78%
“…We identified several orally bioavailable CSF1R inhibitors that noninvasively cross the blood‐brain barrier, leading to brain‐wide microglial elimination within days, which continues for as long as CSF1R inhibition is present (Dagher et al, 2015; Elmore et al, 2014). In particular, removal of CSF1R inhibition stimulates the rapid repopulation of the entire brain with new microglial cells (Elmore et al, 2014; Elmore, Lee, West, & Green, 2015; Rice et al, 2017), effectively replacing the entire microglial tissue. This process takes approximately 14–21 days to complete; thereafter, the new microglia are virtually indistinguishable (i.e., cell densities, morphologies, and gene expression profiles) from the resident microglial tissue.…”
Section: Introductionmentioning
confidence: 99%
“…We have shown that CSF1R inhibitor‐dependent microglial replacement essentially “resets” this “reactive” microglial population, whereby returning microglia resemble nonreactive homeostatic microglia and promote functional recovery (Rice et al, 2017). Thus, microglial elimination and repopulation may be beneficial in situations that implicate altered microglial phenotypes in impaired brain function.…”
Section: Introductionmentioning
confidence: 99%
“…These inflammatory responses are a classic component of the secondary injury cascade and are associated with neuronal death (Corps et al 2015). This neuroinflammation begins in the acute phase but can last for years post-injury in both humans and animals (Johnson et al 2013; Kumar et al 2013; Rice et al 2017; Smith et al 2013). Microglial/macrophages (MG/Mϕ) are the main players in propagating inflammation to tissues neighboring the core site of injury.…”
Section: Introductionmentioning
confidence: 99%